Application of green accounting to company values through profitability - Jayanti, Dwi; Romli, Romli (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The objective of this study is to investigate the impact of the adoption of green accounting practices on the valuation of firms, specifically by analyzing its influence on profitability. This study assesses green accounting through the utilization of two sub-variables: environmental performance, which is evaluated based on the PROPER rating, and disclosure of environmental costs, which is measured using a dummy variable. Additionally, profitability is evaluated by means of Return on Assets (ROA), while company value is determined using Tobin's Q. The research methodology employed in this study is a quantitative approach utilizing an associative research design. The sample for this research comprises non-financial firms that are publicly listed on the Indonesia Stock Exchange (IDX) during the period from 2016 to 2020. The findings indicate that there was only a partial impact of environmental performance and disclosure of environmental costs on profitability. The environmental performance and disclosure of environmental costs have a partial impact on the valuation of firms. The impact of profitability on firm value is limited. There is no discernible impact on firm value through profitability as a result of environmental performance and the disclosure of environmental costs.